Quality of life in people with Parkinson’s disease: the relevance of social relationships and communication - Kayoko Takahashi; Naoto Kamide; Makoto Suzuki; Michinari Fukuda (2016)
[Purpose] Maintaining high quality of life is crucial for the rehabilitation of patients with Parkinson's disease. The quality of life scales currently in use do not assess all quality of life domains or their importance for each individual. Therefore, a new quality of life measure, the Schedule for the Evaluation of Individual Quality of Life-Direct Weighting, was used to investigate quality of life in people with Parkinson's disease. [Subjects and Methods] Fifteen people with idiopathic Parkinson's disaese (average age = 80.0 years, standard deviation = 10.3 years, Hoehn & Yahr stages 1-4) were interviewed using the Schedule for the Evaluation of Individual Quality of Life-Direct Weighting. Its quality of life constructs were tested by comparing them against disease-specific quality of life (39-items Parkinson's Disease Questionnaire), motor functioning (Unified Parkinson's Disease Rating Scale Part III), and activities of daily living (Barthel Index). [Results] Social connections such as "family" and "friends" were revealed as important constructs of life satisfaction. The Schedule for the Evaluation of Individual Quality of Life-Direct Weighting was not significantly correlated with the 39-items Parkinson's Disease Questionnaire, Unified Parkinson's Disease Rating Scale Part III, or Barthel Index but was significantly correlated with the "communication" dimension of the 39-items Parkinson's Disease Questionnaire. [Conclusion] The Schedule for the Evaluation of Individual Quality of Life-Direct Weighting detected various domains of quality of life, especially social relationships with family and friends. "Being heard" was also revealed as an essential component of life satisfaction, as it provides patients with a feeling of acceptance and assurance, possibly resulting in better quality of life.